Simultaneous optical measurements of equatorial plasma bubble (EPB) from Kolhapur (16.8°N, 74.2°E) and Gadanki (13.5°N, 79.2°E) - Ghodpage, R.N.; Taori, A.; Patil, P.T.; Gurubaran, S.; Sripathi, S.; Banola, S.; Sharma, A.K. (My University, 2014)
In this paper, we study the Equatorial Plasma Bubble (EPB) features using All sky imager (ASI) observations of O(1D) 630.0 nm night airglow emission from Kolhapur (16.8°N, 74.2°E, 10.6°N dip lat.) and Gadanki (13.5°N, 79.2°E, 6.5°N dip lat.) during March 2012. The optical data was supported by the ionosonde measurements from Tirunelveli (8.7°N, 77.8°E, 0.5°N dip lat.) which revealed the occurrence of equatorial spread-F. The EPBs were monitored at both locations as nearly north–south aligned intensity depleted regions. We computed east–west plasma drift velocity over Kolhapur and Gadanki for the nights having coordinated measurements. Also, the observed plasma bubble drift velocities are compared with the zonal neutral wind velocities obtained from the HWM-07 model and the empirical drift model of England and Immel (2012). We observed that, generally, the mean zonal drift velocities of the plasma bubbles tend to decrease with local time (after midnight). Our results reveal the drift velocity noted in Kolhapur data varies from 124 m/s to 181.8 m/s, while from the Gadanki data show the drift velocity to range from 116.3 m/s to 160.3 m/s.
Keywords: Ionosphere; Spread-F; EPB; Plasma drift; Equatorial plasma bubble; Kolhapur; Gadanki